Physico-chemical analysis and detection of adulteration in raw milk collected from Goalas of different places of sadar upazila in Mymensingh district - Rahman, Atikur; Habib, Md Rezwanul; Ali, Md Younus; Islam, Mohammad Ashiqul; Rashid, Md Harun ur (Research in Agriculture Livestock and Fisheries, 2017)
This research work was carried out to assess the physical, chemical quality and detection of adulteration in raw milk collected from goals of five different places of Mymensingh sadar upazila (BAU Sheshmore, BAU KR market, train going vendor, sweetmeat shop and Dhudmohol) in Bangladesh. Results shows that milk from sweet meat shop had 100% yellowish white colour, normal (milky) flavor and free flowing liquid whereas other sources milk varies with their percentage in terms of physical parameters. Specific gravity of milk from various sources differed significantly (p<0.01) and all the chemical parameters of milk sample collected from different sources differed significantly (p<0.01). Significantly higher percentage of total solids (12.67±0.10) and fat content (4.36±0.07) was found in milk from goala of sweet meat shop than others. All of the adulteration tests showed negative result that means no adulterant materials was found in the collected milk samples. Considering the results, it could be inferred that there was an ample fluctuation present on qualities of milk samples collected from the goalas of different places of Mymensingh sadar regarding the standard of the parameters and the raw milk samples from sweetmeat shop were of good quality. The results suggested that milk purchase from reliable sources is very much important for consumers due to its quality. Res. Agric., Livest. Fish.4(2): 99-106, August 2017